Fibroblast growth factor receptor signaling plays a key role in transformation induced by the TMPRSS2/ERG fusion gene and decreased PTEN - Shao, Longjiang (Oncotarget, 2018)
Prostate cancer is the most common visceral malignancy and the second leading cause of cancer deaths in US men. Correlative studies in human prostate cancers reveal a frequent association of the TMPRSS2/ERG (TE) fusion gene with loss of PTEN and studies in mouse models reveal that ERG expression and PTEN loss synergistically promote prostate cancer progression. To determine the mechanism by which ERG overexpression and PTEN loss leads to transformation, we overexpressed the TE fusion gene and knocked down PTEN in an immortalized but non-transformed prostate epithelial cell line. We show that ERG overexpression in combination with PTEN loss can transform these immortalized but non-tumorigenic cells, while either alteration alone was not sufficient to fully transform these cells. Expression microarray analysis revealed extensive changes in gene expression in cells expressing the TE fusion with loss of PTEN. Among these gene expression changes was increased expression of multiple FGF ligands and receptors. We show that activation of fibroblast growth factor receptor signaling plays a key role in transformation induced by TE fusion gene expression in association with PTEN loss. In addition, in vitro and in silico analysis reveals PTEN loss is associated with widespread increases in FGF ligands and receptors in prostate cancer. Inhibitors of FGF receptor signaling are currently entering the clinic and our results suggests that FGF receptor signaling is a therapeutic target in cancers with TE fusion gene expression and PTEN loss.